2008
DOI: 10.1016/j.psychres.2007.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Late, but not early, wake therapy reduces morning plasma melatonin: Relationship to mood in Premenstrual Dysphoric Disorder

Abstract: Wake therapy improves mood in Premenstrual Dysphoric Disorder (PMDD), a depressive disorder in DSM-IV. We tested the hypothesis that the therapeutic effect of wake therapy in PMDD is mediated by altering sleep phase with melatonin secretion.We measured plasma melatonin every 30 minutes (18:00 -09:00 h) in 19 PMDD and 18 normal control (NC) women during mid follicular (MF) and late luteal (LL) menstrual cycle phases, and during LL interventions with early wake therapy (EWT) (sleep 03:00-07:00 h)(control conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…The endogenous melatonin rhythm is masked by postural changes [33] and light exposure [34], both of which were well-controlled for in this study. Reduced melatonin in PMDD vs. controls was initially reported [13], [14], but not in a recent study [35]. The reasons for this discrepancy are unclear, but the authors point out differences in radioimmunoassay kits, as well as methods of determining melatonin timing parameters that were assessed either quantitatively based on threshold values [13], [14] or qualitatively based on visual inspection [35].…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous melatonin rhythm is masked by postural changes [33] and light exposure [34], both of which were well-controlled for in this study. Reduced melatonin in PMDD vs. controls was initially reported [13], [14], but not in a recent study [35]. The reasons for this discrepancy are unclear, but the authors point out differences in radioimmunoassay kits, as well as methods of determining melatonin timing parameters that were assessed either quantitatively based on threshold values [13], [14] or qualitatively based on visual inspection [35].…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly considered that exercise improves premenstrual symptoms through elevation of beta-endorphin levels and improved well-being however there is no evidence to confirm this. Small RCTs have suggested efficacy of sleep deprivation and light therapy (Parry et al 2008, see review Shechter and Boivin 2010). These treatments are theorised to regulate circadian rhythms; however the duration of any therapeutic effects, if any, is unclear.…”
Section: Suppression Of Ovulationmentioning
confidence: 99%
“…This finding parallels our previous study of women with PMDD, in which increased melatonin duration was associated with depressive symptoms in the luteal phase, when P 4 is elevated, but not in the follicular phase, when P 4 is absent and women with PMDD are asymptomatic. 39 In a previous study of menopausal women, we also found that DLMOff was delayed in DW compared with HW. 18 Notably, delayed DLMOff is associated with an evening chronotype commonly found in depressive disorders.…”
Section: Melatonin Timing Measuresmentioning
confidence: 49%
“…For example, morning/late-night, but not evening/early-night, wake therapy advances melatonin offset in PMDD. 39 The strengths of this study include careful screening and diagnostic assessments of depression using objective, interview-based assessments by trained mental health professionals in women selected from a broad range of ages, parity, ethnicities, and socioeconomic status, with sampling distributed across the seasons of the year and precise circadian sampling of plasma melatonin. Study limitations include reliance on relatively small samples of women.…”
Section: Implications For Treatment and Researchmentioning
confidence: 99%